1985
DOI: 10.1159/000128461
|View full text |Cite
|
Sign up to set email alerts
|

Standardized Intraabdominal Abscess Formation with Generalized Sepsis: Pathophysiology in the Rat

Abstract: Gelatine capsules containing Escherichia coli and Bacteroides fragilis in a standardized mixture with rat colonic content and barium sulfate were implanted intraabdominally into rats. Capsules of 0.75 g gave approximately 50% mortality whereas 0.35 and 1.10 g caused no or 100% mortality, respectively. In subsequent experiments, using the 0.75 g capsule, all animals became ill with signs of tachypnea, piloerection, low physical activity and hypersecretion of saliva 6–8 h after the implantation. The animals redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The challenge material for the intra-abdominal sepsis development was prepared as previously de scribed in detail [20], In short, septic challenge mate rial was obtained by mixing cultures of Bacieroides fragilis [2.5 X 107 colony-forming units (CFU) per ml] and Escheriehia coli (1.3 X I07 CFU/ml) with adju vant substance (autoclaved rat colonic content and barium sulfate). Both bacterial strains originated from abscesses in humans.…”
Section: Preparation O F Challenge Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The challenge material for the intra-abdominal sepsis development was prepared as previously de scribed in detail [20], In short, septic challenge mate rial was obtained by mixing cultures of Bacieroides fragilis [2.5 X 107 colony-forming units (CFU) per ml] and Escheriehia coli (1.3 X I07 CFU/ml) with adju vant substance (autoclaved rat colonic content and barium sulfate). Both bacterial strains originated from abscesses in humans.…”
Section: Preparation O F Challenge Materialsmentioning
confidence: 99%
“…The aim of the present investigation was to study the early changes in the passage of mac romolecules over the lower respiratory tract into the blood in a rat model of gram-negative sepsis secondary to intra-abdominal bacterial infection [20], BSA (MW = 67,000 D) was used as macromolecular marker and intratracheally instilled to adult rats, and the passage via the respiratory tract was assessed as immunoreactive BSA levels in blood plasma as previously described [16], Studies on the im portance of bacteria for the development of sepsis were also performed.…”
Section: Introductionmentioning
confidence: 99%
“…Animal model data suggested that the encapsulation phase of abscess formation occurs 10-14 days following infection [10] . Oxygen availability and metabolic activity are reduced within abscesses and surrounding encapsulated purulent lesions [11] . The pH of abscess fluid has been reported to range from 5.5 to 7.2 [12][13][14][15] .…”
mentioning
confidence: 99%
“…Generally, Escherichia coli (E.coli) is the strain of bacteria that is mixed with sterilized cecal contents and given to the peritoneum. (14) The main advantage of this model is that the mortality rate is controllable by modifying the dose of E. coli. 3) Endogenous fecal contamination can be achieved by at least two models.…”
Section: Experimental Models To Study the Microcirculation In Sepsismentioning
confidence: 99%